Energy values of traditional ingredients and sugarcane yeast for laying hens - Silva, Demósthenes Arabutan Travassos da; Rabello, Carlos Bôa Viagem; Santos, Marcos José Batista dos; Lima, Michele Bernardino de [UNESP]; Silva, Edney Pereira da [UNESP]; Arruda, Emmanuele Maria Florêncio de; Lopes, Cláudia da Costa (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2014)
An experiment was conducted to determine the chemical composition and apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen balance (AMEn) values of corn, soybean meal (SBM), soybean oil (SO) and sugarcane yeast (SY) (Saccharomyces cerevisiae). A metabolism trial was performed with 120 Dekalb White laying hens at 65 weeks of age, using the method of total excreta collection. Birds were housed in metabolism cages and distributed according to a completely randomized design into five treatments with, six replicates of four birds each. The experimental period consisted of four days of adaptation and four days of excreta collection. The experimental diets included: a reference diet based on corn and SBM and four test diets containing 40% corn, 30% SBM, 10% SO or 30 % SY. The chemical compositions of the tested ingredients, expressed on "as-is" basis were: 86.9, 87.29, 87.32 and 99.5% dry matter; and 3.51, 2.08, 99.31 and 0.03 ether extract for corn, SBM, SO and SY, respectively. Corn, SBM, and SO presented 7.33, 43.61 and 24.64% crude protein, and 0.58, 5.07 and 6.77% ash, respectively; and crude fiber contents of corn and SBM were, respectively, 2.24% and 3.56%. The following AME and AMEn (kcal/kg dry matter) values were obtained: 3,801 and 3,760 kcal/kg for corn, 2,640 and 2,557 kcal/kg for SBM, 8,952 and 8,866 kcal/kg for SO, and 1,023 and 925 kcal/kg for sugarcane yeast, respectively.
Keywords: Corn; Metabolizable energy; Soybean meal; Soybean oil